The Emerging Role of FUNDC1-Mediated Mitophagy in Cardiovascular Diseases - Liu, Lei; Li, Yimei; Chen, Quan (Frontiers in Physiology, 2021)
Mitochondria are highly dynamic organelles and play essential role in ATP synthase, ROS production, innate immunity, and apoptosis. Mitochondria quality control is critical for maintaining the cellular function in response to cellular stress, growth, and differentiation Signals. Damaged or unwanted mitochondria are selectively removed by mitophagy, which is a crucial determinant of cell viability. Mitochondria-associated Endoplasmic Reticulum Membranes (MAMs) are the cellular structures that connect the ER and mitochondria and are involved in calcium signaling, lipid transfer, mitochondrial dynamic, and mitophagy. Abnormal mitochondrial quality induced by mitophagy impairment and MAMs dysfunction is associated with many diseases, including cardiovascular diseases (CVDs), metabolic syndrome, and neurodegenerative diseases. As a mitophagy receptor, FUNDC1 plays pivotal role in mitochondrial quality control through regulation of mitophagy and MAMs and is closely related to the occurrence of several types of CVDs. This review covers the regulation mechanism of FUNDC1-mediated mitophagy and MAMs formation, with a particular focus on its role in CVDs.